The effect of weight training on the physical performance of Boxers at junior level of Kaithal District (Haryana, India) - Solanki, Ajay (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The main purpose of the study is to know the effects of weight training programme on the physicalperformance of boxers at junior level of Kaithal district. For the purpose of the study 10 selected exercisesof weight training along with warming up and cooling down exercises schedule of one hour's and one andhalf an hour in both morning and evening session were used. The investigator himself with the help of hiscolleagues implemented training schedule for 10 weeks to experiment group consisting of 20 boxers. Thetraining designed in such a way that physical fitness required for the boxing situations, ranging fromtechnical and tactical requirement for the boxers. To develop physical fitness, the training of physicalparameters like strength, power and endurance spread over a number of years. But due to variousconstraints and restrain on the investigator, the training of weight was confined to 10 weeks only. Thedata was collected of we and post test of the boxers appeared in the physical fitness components testgiven in the preceding paras. Boxer whatever their weight categories are, they need physical efficiency and fitness elements as theyhave to fight against the odds in the boxing ring. They are to contribute physically for completecoordination among themselves. The boxers get no respite in the course of bout when fighting or dagingboxing in the ring. Boxers requires great stamina, speed, endurance, flexibility and agility with greateramount of strength and power and to meet the demand, it has to be cultivated through proper exercisesnot only during preparatory phases or stages but one's long boxing career. In addition with relaxation andoptimum workload through weight during competition period, one has to maintain vigor and stamina andspeed. Which is a matter of training while strength can be earned through light weight exercises andsquats with weight and with carrying of dumbbells etc.